Critical Success Factors and Challenges Encountered in a Safe City by Selected Medium Enterprises in Manila, Philippines - Marzo-Catu, Rosalie Marzo-Catu (Journal of Interdisciplinary Perspectives, 2025)
This study investigates urban safety from the perspective of medium-sized enterprises (SMEs) in dynamic city environments, addressing a gap in existing research, which often focuses on larger corporations or general strategies. The study identifies critical success factors (CSFs) such as law enforcement, infrastructure, social cohesion, and tailored safety resources by understanding SMEs' specific needs and challenges. The study used a descriptive design with quantitative data from 50 SME owners and 50 barangay officials in Manila through a modified CSF-based questionnaire. Results highlight the importance of planning, communication, skills, tools, processes, management, and teamwork in creating safer urban environments, with respondents agreeing on their relevance regardless of demographic differences. SMEs face limited resources, a lack of coordinated strategies, and insufficient city support. Notably, a strong relationship exists between the assessment of CSFs and these challenges. Policymakers are advised to enhance security measures, support community participation, provide training, and encourage collaboration between businesses and authorities. These findings provide valuable insights for developing policies that foster SME growth while promoting safer and more prosperous urban environments.